Constructing electron transport channel of SnO2/BaSO4 on g-C3N4 for enhanced visible-light-driven photocatalytic H2 production - Gongyue Dong; Xiaojuan Guo; Cheng Cheng; Feng Chen; Jinfeng Zhang; Yanping Du; Wei Meng; Maochang Liu; Jinwen Shi (Materials Today Catalysis)
Graphitic carbon nitride (g-C3N4) is confronted with the issue of poor utilization of photogenerated charge carriers, thereby leading to limited performance of photocatalytic hydrogen (H2) production, which restricts its potential application. Herein, the electron transport material SnO2/BaSO4 was synthesized to integrate with g-C3N4 for addressing the above problem. Various characterizations were conducted to investigate the g-C3N4-SnO2/BaSO4 photocatalyst, and it demonstrated that photogenerated electrons from g-C3N4 expeditiously migrate to SnO2/BaSO4 nanoparticles, which markedly hindered photogenerated carriers’ recombination. Subsequently, the g-C3N4-SnO2/BaSO4 photocatalyst demonstrated promoted photocatalytic H2 production at a rate of 14.2 μmol h−1 under visible-light illumination, which was 2.5 times higher than that of pristine g-C3N4.